Advances in practical applications of scalable multi-agent systems : the PAAMS collection : 14th International Conference, PAAMS 2016, Sevilla, Spain, June 1-3, 2016, Proceedings /: the PAAMS collection : 14th International Conference, PAAMS 2016, Sevilla, Spain, June 1-3, 2016, Proceedings. (2016) - Unknown
No abstract available